Procedure for issuing Polandandri Marriage Certificate at KUA (Case Study of the Issuance of Marriage Certificate of Polyandri Actors) - Maswandi Maswandi (Proceeding International Seminar of Islamic Studies, 2019)
The purpose of this study was to explore the procedure for issuing a polyandry deed at KUA (Office of Religious Affairs). The object of research is the procedural issuance of the deed of polyandry. This type of research is descriptive qualitative. Where the various phenomena found will be analyzed qualitatively and objectively. The method of collecting data in research uses library research and interviews with several related parties. Analysis of the data used is descriptive by using literature studies in the form of books both Civil Law and fiqh munakahah including fatwas. The results show that the Ministry of Religion has established various procedures related to the implementation of marriage and polygamy which are selective that must be obeyed by every Muslim to do polygamy. The Religious Courts have an important role in fulfilling polygamy procedures. However, there is still a possibility that polyandri marriages will occur due to administrative negligence and / or forgery that has been carried out either by various